Estrategia didáctica LUDIMAT y creatividad matemática en estudiantes del tercero de primaria de la institución educativa “Miguel Grau” de Casa Grande - 2011 - Gonzalez Toribio, Elsa María (2019)
ABSTRACT The present research work has been developed with the purpose of improving Mathematical Creativity in the students of the Third Degree of Primary of the Educational Institution N ° 81515 "Miguel Grau" of Casa Grande, through the application of the LUDIMAT Teaching Strategy. The type of study of the research was quantitative and with experimental design, the population for the research consisted of 126 students and the sample of the study conformed by 56 students, of which 28 were members of the Experimental Group and 28 the Control Group; As initial and final measurement instruments, the Test about mathematics creativity. Then the LUDIMAT Teaching Strategy was developed, in a period of three months, structured in 07 class sessions that present diverse situations of play through which problems are posed and solved. According to the results obtained, it was possible to demonstrate that, when applying the LUDIMAT Educational Strategy, Mathematical Creativity was significantly improved in the third grade students of the "Miguel Grau" Educational Institution of Casa Grande.